Myocardial revascularization: factors intervening in the reference and counter-reference in the hospital setting - Kamylla Santos da Cunha; Carolina Kahl; Cintia Koerich; Gabriela Marcellino de Melo Lanzoni; Alacoque Lorenzini Erdmann; Betina Hörner Schlindwein Meirelles
ABSTRACT Objective: To understand the intervening factors in the process of reference and counter-reference of the individual with heart disease in the scenario of high complexity in the health care network. Method: Research anchored in the Grounded Theory (Teoria Fundamentada nos Dados). It totaled 21 participants. The data collection scenario was a cardiovascular reference hospital in the south of Brazil and occurred between March and June 2014. Results: The intervening factors in the reference process were the difficulty to access the points of the network and telemedicine and the central to manage the flow of patients in the network. In the counter-reference, there was a link with the hospital and the lack of communication among network professionals. Conclusion: It reveals the need to reorganize the service flow in HCN, enhancing PHC, expanding the performance of medium complexity and increasing the capacity of high complexity in order to carry out the process of reference and counter-reference.